2021
DOI: 10.1158/1078-0432.ccr-19-2163
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM7 Is an Effective Target for CAR T-cell Therapy of Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: To investigate whether CEACAM7 represents a novel therapeutic target for treating pancreatic ductal adenocarcinoma (PDAC) and to generate CEACAM7-targeting CAR T cells to test this hypothesis.Experimental Design: We identified CEACAM7 (CGM2), a member of the CEA family of proteins with expression restricted to the colon and pancreas, as a potential CAR T-cell target for PDAC. We probed a panel of PDAC tumor sections as well as patient-derived PDAC cell cultures for CEACAM7 expression. We generated CAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…However, down-regulation of CEACAM7 in hyperplastic polyps and early adenomas represent some of the earliest observable molecular events leading to colorectal tumors ( Scholzel et al, 2000 ). Though CEACAM7 expression was thought to be restricted to the epithelial cells of the colon and pancreas, according to the Human Protein Atlas, grandular cells of the breast have moderate CEACAM7 protein expression ( Uhlen et al, 2015 ; Raj et al, 2021 ). How CEACAM7 plays a role in breast cancer is currently unknown, but the link could even be indirect and due to expression in non-breast tissue ( Ferreira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, down-regulation of CEACAM7 in hyperplastic polyps and early adenomas represent some of the earliest observable molecular events leading to colorectal tumors ( Scholzel et al, 2000 ). Though CEACAM7 expression was thought to be restricted to the epithelial cells of the colon and pancreas, according to the Human Protein Atlas, grandular cells of the breast have moderate CEACAM7 protein expression ( Uhlen et al, 2015 ; Raj et al, 2021 ). How CEACAM7 plays a role in breast cancer is currently unknown, but the link could even be indirect and due to expression in non-breast tissue ( Ferreira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The well-known PDAC tumor-associated antigens, such as CEA, EGFR, Her2, MUC1, and mesothelin, are targeted for CAR-T development [ 156 ]. Recently, a team led by John F. Marshall developed and demonstrated the clinical potential of the carcinoembryonic antigen-related cell adhesion molecule 7 (CEACAM7)—a novel target for CAR-T development for PDAC treatment with promising outcomes [ 157 ]. Pre-conditioning strategies, such as optimizing the TH2-TH1 ratio, depletion of Tregs, and increasing macrophage activation for enhancing CAR-T cell therapy, have also been investigated [ 156 ].…”
Section: Pdac Therapeutics and Tumor Microenvironmentmentioning
confidence: 99%
“…Thus, it was concluded that bi-specific CAR-NK cells may prove a promising immunotherapeutic when combined with 125 I seed therapy in treatment of pancreatic cancer. Identification of novel antigens for therapy are useful strategies for cell-based therapy[ 83 , 84 ].…”
Section: Nk Cells As Therapy In Pdacmentioning
confidence: 99%